PERSEPSI PERAWAT TERHADAP PEMANFAATAN REKAM MEDIS ELEKTRONIK DALAM MENDUKUNG MANAJEMEN PELAYANAN DI RSUD dr. REHATTA - Yohana, Yohana; Asgiani, Piping (Dian Nuswantoro Semarang, 2025)
Electronic Medical Records (EMRs) are beneficial in improving patient care management in healthcare facilities. RSUD dr. Rehatta, Central Java Province, has implemented EMRs since 2023, but no evaluation has yet been conducted regarding nurses' satisfaction with their utilization. This study is descriptive with a qualitative approach. The research design is a case study, and data were collected through in-depth interviews with seven informants. The content dimension was rated as less satisfactory due to the complexity of the anamnesis module. The accuracy dimension did not fully meet user expectations. The format dimension was also rated as suboptimal due to inefficiencies. The timeline dimension was considered good, while the ease of use dimension was rated positively, as data entry was deemed simple. The implementation of the Inova system in the outpatient clinic of RSUD dr. Rehatta has shown benefits, but some user complaints remain. Immediate improvement strategies include simplifying content, reducing information delivery delays, and enhancing system usability.